(untitled) (Research, Society and Development, 2020)
Objective: to describe the profile of mortality from diseases of the circulatory system in the city of Rio de Janeiro / RJ from 2010 to 2014. Methodology: this is a descriptive, ecological, documentary and retrospective study carried out with data from the mortality information system, according to gender, age group, color / ethnicity, educational level, marital status, place and year of occurrence of deaths in the period from 2010 to 2014, years available for analysis. Results: 187,029 deaths from diseases of the circulatory system were recorded in the state of Rio de Janeiro (which has 92 municipalities in total) and, in the state capital, 76,684 were recorded, corresponding to 40% of deaths. Regarding gender, the highest number of deaths occurred in women (51.6%). The year 2010 showed the highest overall mortality rate (851.9 deaths per 100,000 inhabitants) and 2012 had the lowest proportional mortality (238.3 per 100,000 inhabitants). Among the diseases of the circulatory system, the main specific causes of mortality include acute myocardial infarction (26.6%), stroke (10.1%) and essential hypertension (9.4%). Conclusion: even with the decline in mortality rates due to circulatory diseases, the absolute number of these deaths is still high. Therefore, there is a need to implement public health policies with an emphasis on preventing new cases of circulatory diseases. Encouraging health promotion, so that there is involvement between managers, health professionals and SUS users.